Elaboración de un acaricida natural a base de aceite esencial de ruda (Ruta graveolens) para el control de Varroasis (Varroa jacobsoni oudemans) en abejas (Apis mellifera) y su incidencia en la producción de miel en el barrio Landangui de la parroquia Malacatos del cantón Loja - Balcázar Chamba, Máximo Bolívar (2016)
In this paper the alternative control of Varroa which is a very dangerous disease of bees, which depresses immune and can cause death of hives causing significant economic losses were evaluated. In this study two treatments for varroa at (40% and 50%) concentration of essential oil of Ruta graveolens in ten beehives divided into two experimental groups, each hive represents an experimental unit, which was conducted in the period of titrated May to September 2015. the analysis was conducted in three phases: first to strengthen food in all hives achieving homogenize the population, the second to determine the percentage of infestation in the two apiaries, and the third the results were analyzed obtained at the end of the investigation to determine what treatment was more effective. The percentage of infestation at the start of research on adult bees was 14.10% on average of the two experimental groups. The greater effectiveness of essential oil obtained rough treatment the two with a 79.77%, treating one obtained 59.42% effectiveness. From the results obtained, the last two applications are highly significant and the first two showed no significant difference Duncan test. In conclusion, varroa treatment must be made a health protocol according to the time of year and the percentage of infestation. The profitability of Ruta graveolens essential oil is favorable for beekeepers in the area, despite being expensive treatment, but it is effective, harmless and does not affect the environment and to the products of the hive. In addition it can be applied at any time of year. Keywords: Beehive, Essential Oil, Food, Varroa, Reps.